The great ark: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story recounts the construction of Noah's ark, where he gathers pairs of animals in preparation for the impending flood. It symbolizes faith, obedience to God's command, and the promise of salvation amidst adversity.